Aceh’s Local Elite Power Strategy - Mursyidin Mursyidin; Vellayati Hajad; Ikhsan Ikhsan (Universitas Muhammadiyah Yogyakarta, 2022)
This paper aims to see how the strategy of local elites in gaining power in village government in Aceh. In this case, Acehnese local elites, former members of the Free Aceh Movement (GAM), have economic and political advantages over other communities because they have networks within the Free Aceh Movement organization down to the grassroots. The qualitative method with the case study approach was used in this research. The findings of this study revealed that local Acehnese elites used the connections of fellow GAM members in the government as a strategy to seize economic and political resources in the village. They contested in the village head election (keuchik) and competed to become village government officials after knowing the number of village funds managed by the village through general elections and even through direct appointment as interim village head officials. This study concludes with four main strategies for gaining power in government in the village. The main strategies are (1) successful team consolidation, (2) segmentation, targeting, and positioning, (3) candidate image, and (4) Aceh's contextual strategy in the form of a network of the former Free Aceh Movement in gaining political power at the village level in Aceh.